2004
DOI: 10.1016/j.dental.2003.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 3-methacryloxypropyltrimethoxysilane and vinyltriisopropoxysilane blend and tris(3-trimethoxysilylpropyl)isocyanurate on the shear bond strength of composite resin to titanium metal

Abstract: The effect of a 3-methacryloxypropyltrimethoxysilane and vinyltriisopropoxysilane blend and tris(3-trimethoxysilylpropyl)isocyanurate on the shear bond strength of composite resin to titanium metal Jukka P. Matinlinnaa, Jukka P.; Özcan, Mutlu; Lassilaa, Lippo V.J.; Vallittua, Pekka K. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 25 publications
2
75
1
1
Order By: Relevance
“…The substantial reduction in bond strength values due to thermo-cycling for all specimen groups can be partially explained by the more than 6-fold difference between thermal expansion coefficients of the experimental methacrylate resin (approximately the value for acrylic denture resin, about 76/°C×10 6 ) and Ti, (about 12/°C ×10 6 ) [25]. The shear bond strength results obtained in this study are lower than those reported in our previous studies of resin bonding to silica-coated Ti [14][15][16]18], as well as those in studies in which a silane blend produced significantly stronger bonding that functional silanes alone [18,20,21]. The three bifunctional silanes in this study were used without further purification by re-distillation, which may have contributed to reduced performance.…”
Section: Resultscontrasting
confidence: 54%
See 4 more Smart Citations
“…The substantial reduction in bond strength values due to thermo-cycling for all specimen groups can be partially explained by the more than 6-fold difference between thermal expansion coefficients of the experimental methacrylate resin (approximately the value for acrylic denture resin, about 76/°C×10 6 ) and Ti, (about 12/°C ×10 6 ) [25]. The shear bond strength results obtained in this study are lower than those reported in our previous studies of resin bonding to silica-coated Ti [14][15][16]18], as well as those in studies in which a silane blend produced significantly stronger bonding that functional silanes alone [18,20,21]. The three bifunctional silanes in this study were used without further purification by re-distillation, which may have contributed to reduced performance.…”
Section: Resultscontrasting
confidence: 54%
“…A hydrolysis time of 23 h was selected for the crosslinking silane and 1 h was selected for functional silanes because functional trialkoxy silanes hydrolyze sufficiently within 1 h [16][17][18][19][20][21]. Formic acid was used as the catalyst, and it has some similarities with acetic acid, which has been used in past studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations